IMPROVING STUDENTS’ LEARNING OUTCOMES IN BIOLOGY THROUGH THE CONTEXTUAL TEACHING AND LEARNING MODEL BY YEAR VII-A STUDENTS OF MTsN 1 WEST ACEH - Nurmailis Nurmailis (FKIP Universitas Al Washliyah Medan, 2021)
This study aims to determine